Isoniazid-induced Tenosynovitis: A Rare Case Report - Piyush Kumar Jain; Pradeep Nirala; Mazher Maqusood; Ravi Shankar Mishra; Abhishek Kumar; Pooja Sindwani; Ravindra Nath (Acta Medica International)
The presentation of pain and numbness in flexor tendons of wrist in a patient on anti-tuberculosis treatment (ATT) with isoniazid should raise a suspicion for possible tenosynovitis. Commonly, tenosynovitis affects the wrist, hand, and fingers, although it can occur in any tendon sheath in the body. This is a case report illustrates the occurrence of tenosynovitis in a 60-year-old female subsequent to the initiation of anti-tubercular therapy (ATT) containing isoniazid (INH). The patient presented 2 weeks, without a history of trauma. Clinical examination and diagnostic work-up confirmed tenosynovitis, ruling out other causes of musculoskeletal symptoms. Although rare, INH-induced tenosynovitis should be considered, especially in patients with normal uric acid and rheumatoid arthritis factor levels. Regular monitoring for musculoskeletal side effects during ATT is crucial for timely detection and management. The objective of this case report is to highlight the rare occurrence of INH-induced tenosynovitis and emphasize the importance of its early detection and treatment.